Discourse and Power: Persuasive Language in Indonesian Media - Hadiwijaya, Munawwir (Verba: Journal of Applied Linguistics, 2023)
The discourse in Indonesia media today has a significant impact on public opinion and attitudes, so it is important to investigate the subtle dynamics of persuasive communication. In order to better understand how the combination of various language structures affects the effectiveness of persuasive verbal contact, this study looks at the idea of synergistic pragmatic effects. This study employs a strong functional-linguistic methodology and uses a corpus of opinion pieces and newspaper articles from both American and British publications. It analyzes linguistic devices like metaphor, irony, comedy, emotionally charged lexemes, hyperbole, interdiscursive references, and rhetorical questions using both qualitative and quantitative methods. The results demonstrate the transformative potential of skillfully applied synergy in accomplishing communication objectives and improving message perception. Different language patterns interact to elicit specific cognitive and affective responses from audiences, influencing how they understand the information that is being delivered. The area where teaching English as a foreign language for cross-cultural professional communication has the greatest immediate application of this research's practical implications. Through combining components of critical thinking, media literacy, functional-linguistic analysis, and language proficiency, learners are better equipped to recognize and resist speech manipulation in media texts. This study adds to the body of knowledge already available on the subject of language's function in media communication and emphasizes the need for more investigation into the relationship between discourse, language, and persuasion in media.